The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2147/ijn.s88508
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cellular responses upon interaction with silver nanoparticles

Abstract: In order for nanoparticles (NPs) to be applied in the biomedical field, a thorough investigation of their interactions with biological systems is required. Although this is a growing area of research, there is a paucity of comprehensive data in cell-based studies. To address this, we analyzed the physicomechanical responses of human alveolar epithelial cells (A549), mouse fibroblasts (NIH3T3), and human bone marrow stromal cells (HS-5), following their interaction with silver nanoparticles (AgNPs). When compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…In this work, we found that a typical model of alveolar epithelial cell exposed to Fe 2 O 3 and TiO 2 NPs presented a reduction in cell stiffness. From previous studies, Subbiah et al (2015) reported an increase in cell stiffness after exposure to silver NPs in several cell types including A549 cells, human bone marrow stromal cells (H-S5) and breast cancer cells (NIH3T3). However, the dose employed by these authors was the highest tested here (40 μg/mL of NPs), which presented clear cytotoxic effects on all the three types of cells used.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we found that a typical model of alveolar epithelial cell exposed to Fe 2 O 3 and TiO 2 NPs presented a reduction in cell stiffness. From previous studies, Subbiah et al (2015) reported an increase in cell stiffness after exposure to silver NPs in several cell types including A549 cells, human bone marrow stromal cells (H-S5) and breast cancer cells (NIH3T3). However, the dose employed by these authors was the highest tested here (40 μg/mL of NPs), which presented clear cytotoxic effects on all the three types of cells used.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AFM is a powerful tool to analyze the interaction between the cells and AgNPs at high accuracy. In this respect, Subbiah et al employed AFM to investigate the physicomechanical responses of A549, human bone marrow stromal cells (HS-5) and mouse fibroblasts (NIH3T3) exposed to AgNPs [226]. Bioassays (CCK-8, GSH, and lipid peroxidation) were also concurrently performed.…”
Section: In Vitro Cell Cultivationmentioning
confidence: 99%
“…NP: nanoparticles; Y. M.: Young’s modulus. Reproduced from [226] with permission of Dove Medical Press Ltd.…”
Section: Figurementioning
confidence: 99%
“…In addition, the type of reducing agents used for the synthesis of AgNPs is a crucial factor for the determination of cytotoxicity. 1 , 26 Dissolved Ag cations are biochemically active agents that interfere with bacterial cell membrane permeability and cellular metabolism. Ag also contributes to the formation of reactive oxygen species and other mechanisms that potentially affect prokaryotic cells.…”
Section: Discussionmentioning
confidence: 99%